ÐÐºÑÐ¿ÐµÑ€Ð¸Ð¼ÐµÐ½Ñ‚Ð°Ð»ÑŒÐ½Ð¾Ðµ Ð¸Ð·ÑƒÑ‡ÐµÐ½Ð¸Ðµ ÑÐ¾ÑÑ‚Ð¾ÑÐ½Ð¸Ñ Ð¿Ñ€Ð¾Ð¾ÐºÑÐ¸Ð´Ð°Ð½Ñ‚Ð½Ð¾-Ð°Ð½Ñ‚Ð¸Ð¾ÐºÑÐ¸Ð´Ð°Ð½Ñ‚Ð½Ð¾Ð³Ð¾ Ð±Ð°Ð»Ð°Ð½ÑÐ° Ð¶Ð¸Ð²Ð¾Ñ‚Ð½Ñ‹Ñ… Ð² Ð´Ð¸Ð½Ð°Ð¼Ð¸ÐºÐµ Ð¸Ð½Ð´ÑƒÑ†Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð½Ð¾Ð³Ð¾ Ð³ÐµÐ½ÐµÑ€Ð°Ð»Ð¸Ð·Ð¾Ð²Ð°Ð½Ð½Ð¾Ð³Ð¾ Ð¿Ð°Ñ€Ð¾Ð´Ð¾Ð½Ñ‚Ð¸Ñ‚Ð° Ð¸ ÐµÐ³Ð¾ ÐºÐ¾Ñ€Ñ€ÐµÐºÑ†Ð¸Ñ ÐºÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð½Ñ‹Ð¼ ÑÐºÑÑ‚Ñ€Ð°ÐºÑ‚Ð¾Ð¼ Ð¿Ð»Ð°Ñ†ÐµÐ½Ñ‚Ñ‹ Ñ‡ÐµÐ»Ð¾Ð²ÐµÐºÐ° - Kutsevlyak, V. F.; Grischenko, V. V.; Nikitchenko, J. V. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2008)
It has been established that the administration of the cryopreserved human placenta extract to animals with induced generalized periodontitis normalized hyperconcentration of lipidsâ€™ hydroperoxides in blood plasma, content of LPO products and activity ofÂ  ascorbate-induced LPO in liver homogenates. Activity of glutathione-peroxidase in blood plasma and liver increased a lot in comparison with its low level during the pathology development.